Genetic diversity in Mexican creole donkeys - Domínguez-Viveros, Joel (2022)
The aim of this study was to evaluate the genetic diversity of the Mexican criollo donkey with SNP-type genetic markers. Sixteen individuals (eight males and eight females) were randomly sampled and genotyped using the GGP Equine 70K chip (71 947 loci). Within chromosome the polymorphic SNPs were identified, determining the expected (He) and observed (Ho) heterozygosity, polymorphic information content (PIC), the fixation index (FIS) and the Hardy-Weinberg equilibrium (HW). Linkage disequilibrium was assessed based on the correlation (r2) between frequencies across loci. An analysis of molecular variance (AMOVA) and a cluster study were performed to infer the number of clusters (k). It was found that 3579 loci (4.9%) presented genetic variability, but 24.9% presented HW disequilibrium (p<0.05). Across chromosomes, the number of polymorphic loci ranged from 50 to 269 with a mean of 115. The (within chromosome) means for PIC and FIS ranged from 0.222 to 0.267 and -0.392 to -0.208, respectively. In all chromosomes Ho was superior to He. For r2, the mean values within chromosome were greater than 0.10; the optimal k corresponded to 2. In the AMOVA, the genetic variability within individuals explained 67%. The SNPs identified as polymorphic make up a first panel of genetic markers for the Mexican creole burro, and the estimated genetic variability can be used in development and conservation schemes.